Analisis Kemampuan Penalaran Matematis Siswa SMP dalam Menyelesaikan Soal Open-Ended pada Materi Teorema Pythagoras - Fadilah Gustin Khainingsih; Maimunah Maimunah; Yenita Roza (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The purpose of this research is to analyze the mathematical reasoning ability of students when solving open-ended problems. The research method used was descriptive qualitative with a case study approach. The subject was as many as 15 students of a grade VIII-2 of SMPN 6 Mandau. The technique of collecting data in this research was a written test. Data analysis techniques were scoring, presenting data, and describing and drawing conclusions from the data collected.  The result of the study showed that the mathematical reasoning ability of the students was very determined when students solved problems, especially the open-ended problems. It could be demonstrated from the achievement of indicators of mathematical reasoning ability, drew a logical conclusion with the medium category, made analogy and generalization with very low categories as well as examining the validity of the statements with low categories. From the achievement of these indicators, it can be concluded that the average mathematical reasoning ability of students still is still categorized into low category. This is because students are still not accustomed of solving open-ended problems.